Pre-service Physics Teachers’ Knowledge, Decision Making, and Self-system Toward Energy Conservation (Jurnal Pendidikan Fisika Indonesia, 2018)
Along with the increase of world’s energy need in one hand and of the impact of its uses in the other hand, conservation is indispensable. This paper describes pre-service physics teachers’ knowledge about energy conservation, how they use their knowledge to make energy-related decisions, and how their self-system toward energy conservation. The data presented here are from selected items of a field test of instrument intended to measure energy literacy that involved 123 pre-service physics teachers from three state universities in Indonesia. They are one state university in South Sumatera and two state universities in West Java. Data from this survey study were analyzed qualitatively. Results showed that pre-service physics teachers were still lack of knowledge and knowledge utilization to make energy-related decision. However, they showed a tendency to engage in energy conservation efforts.Seiring meningkatnya kebutuhan energi dunia di satu sisi dan dampak penggunaannya di sisi lain, konservasi menjadi sangat penting. Artikel ini menggambarkan pengetahuan mahasiswa calon guru fisika tentang konservasi energi, bagaimana mereka menggunakan pengetahuan tersebut untuk mengambil keputusan, dan bagaimana self-system mereka terkait konservasi energi. Data diperoleh dari uji lapangan terhadap instrumen yang ditujukan untuk mengukur literasi energi yang melibatkan 123 mahasiswa calon guru fisika dari tiga perguruan tinggi negeri di Indonesia. Ketiga universitas negeri tersebut adalah satu berada di Sumatera Selatan, dan dua berada di Jawa Barat. Data dari penelitan survey ini dianalisis secara kualitatif. Hasil analisis menunjukkan mahasiswa calon guru fisika kurang dalam pengetahuan dan penggunaan pengetahuan untuk membuat keputusan terkait energi. Namun demikian, mereka menunjukkan kecenderungan untuk terlibat dalam upaya konservasi energi.